Energy Management Strategy Design for Dual-motor Coaxial Coupling Propulsion Electric City-buses. (October 2018) - Zhao, Mingjie; Shi, Junhui; Lin, Cheng
Abstract: A practical dual-motor coaxial coupling propulsion system for electric city-buses and an extraction method for optimal energy management strategy are proposed. The powertrain configuration of the dual-motor coaxial coupling propulsion bus (DMCEB) is illustrated. To research the energy-saving strategy of DMCEB, the comprehensive state and cost functions are established. Then dynamic programming (DP) algorithm is adopted to find the global optimal energy management strategy including the transmission shift schedule, the torque split ratio and the operating points of the two motors. Since the DP-based strategy is hardly implemented in real vehicle directly, a novel application-oriented optimal rule-based strategy is extracted from the DP results by utilizing non-linear support vector machine (SVM) classifier, K-means clustering and piecewise polynomial fitting methods. The extracted strategy is used to redesign and improve the preliminary rule-based strategy, which can decouple the online calculation and offline application parts. The simulation results demonstrate that the extracted strategy is only around 10% worse than that based on DP results. However, it can be executed online easily due to its simplified polynomial form.